Peri-implant biomechanical responses to standard, short-wide, and double mini implants replacing missing molar supporting hybrid ceramic or full-metal crowns under axial and off-axial loading: an in vitro study - Lamiaa Said Elfadaly; Lamiaa Sayed Khairallah; Mona Atteya Al Agroudy (SpringerOpen, 2017)
Abstract Background The aim of this study was to evaluate the biomechanical response of the peri-implant bone to standard, short-wide, and double mini implants replacing missing molar supporting either hybrid ceramic crowns (Lava Ultimate restorative) or full-metal crowns under two different loading conditions (axial and off-axial loading) using strain gauge analysis. Methods Three single-molar implant designs, (1) single, 3.8-mm (regular) diameter implant, (2) single, 5.8-mm (wide) diameter implant, and (3) two 2.5-mm diameter (double) implants connected through a single-molar crown, were embedded in epoxy resin by the aid of a surveyor to ensure their parallelism. Each implant supported full-metal crowns made of Ni-Cr alloy and hybrid ceramic with standardized dimensions. Epoxy resin casts were prepared to receive 4 strain gauges around each implant design, on the buccal, lingual, mesial, and distal surfaces. Results were analyzed statistically. Results Results showed that implant design has statistically significant effect on peri-implant microstrains, where the standard implant showed the highest mean microstrain values followed by double mini implants, while the short-wide implant showed the lowest mean microstrain values. Concerning the superstructure material, implants supporting Lava Ultimate crowns had statistically significant higher mean microstrain values than those supporting full-metal crowns. Concerning the load direction, off-axial loading caused uneven distribution of load with statistically significant higher microstrain values on the site of off-axial loading (distal surface) than the axial loading. Conclusions Implant design, superstructure material, and load direction significantly affect peri-implant microstrains.